Pengaruh Social Media Marketing terhadap Keputusan Pembelian yang Dimoderasi Oleh Kualitas Produk - Zamani N F, Sri Deva; Mulyaningsih, Hendrati Dwi; Permana, Rezi Muhamad Taufik (Bandung Conference Series: Business and Management, 2023)
Abstract. This research focuses on the variables of social media marketing, purchasing decisions, and product quality. The purpose of this study was to determine the relationship between social media marketing and purchasing decisions and the role of product quality as a moderating variable in skincare Somethinc on the TikTok application.The method used in this study is a survey method with a questionnaire instrument as a data collection technique. The object of this research is Somethinc skincare users in the TikTok application who are domiciled in Bandung, totaling 270 people. The sampling technique in this study used purposive sampling. There are two hypotheses in this study. To test the hypothesis, the techniques used are simple regression analysis and MRA (Moderated Regression Analysis). The results of this study indicate that there is a positive and significant influence of social media marketing on consumer purchasing decisions for Somethinc skincare. Furthermore, product quality strengthens the relationship between social media marketing and purchasing decisions for skincare Somethinc on the TikTok application. Abstrak. Penelitian ini berfokus kepada variabel social media marketing, keputusan pembelian, dan kualitas produk. Tujuan dari penelitian ini ialah untuk mengetahui hubungan antara social media marketing dan keputusan pembelian serta peran kualitas produk sebagai variabel moderasi pada konsumen skincare Somethinc di aplikasi TikTok. Metode yang digunakan pada penelitian ini ialah metode survei dengan instrumen kuesioner sebagai teknik pengumpulan datanya. Objek pada penelitian ini ialah pengguna skincare Somethinc di aplikasi TikTok yang berdomisili di Bandung berjumlah 270 orang. Teknik sampling dalam penelitian ini menggunakan purposive sampling. Terdapat dua hipotesis yang ada pada penelitian ini. Untuk menguji hipotesis, teknik yang digunakan yaitu analisis regresi sederhana dan MRA (Moderated Regression Analysis). Hasil dari penelitian ini menunjukkan bahwa terdapat pengaruh positif dan signifikan antara social media matketing terhadap keputusan pembelian pada konsumen skincare Somethinc. Selanjutnya, kualitas produk memperkuat hubungan antara social media marketing terhadap keputusan pembelian pada skincare Somethinc di aplikasi TikTok.